Experimental investigation on FRP-reinforced surface cracked steel plates subjected to cyclic tension. Issue 24 (17th December 2021) - Li, Zongchen; Jiang, Xiaoli; Hopman, Hans; Zhu, Ling; Liu, Zhiping; Tang, Weiguo
Abstract: Surface cracked steel plates reinforced with single-side Fiber-Reinforced Polymer (FRP) subjected to cyclic tension are experimental studied. The main purpose is to analyze the effect of FRP reinforcement on the crack growth. The failure modes and their effects are analyzed as well. Given the single-side reinforcement, reinforcing the cracked surface significantly prolonged the fatigue life, while reinforcing the reversed side resulted in the opposite consequence. Most specimens did not encounter debonding failures, indicating such failures are avoidable by improving the reinforcement quality. The results also indicate the bond layer number is an insensitive factor – an optimum number is existed.